Fragments and debris of the original temple - Temples of India Project Team (Jio Institute, 2024)
Broken fragments and debris from the original temple assembled on the north face of the adhisthana. The fragments assembled here were once part of the original temple, and other subsidiary structures of the Panchayatana plan.